L-valine derived from the gut microbiota protects sepsis-induced intestinal injury and negatively correlates with the severity of sepsis - Chen, Yifan; Sun, Keyuan; Qi, Yue; Tang, Jianguo; Zhu, Haiyan; Wang, Zetian (Frontiers in Immunology, 2024)
The protective role of gut microbiota and its metabolites against intestinal damage in sepsis patients remain unclear.Methods: Fecal samples were acquired from patients categorized into sepsis and non-sepsis groups for analysis of microbial composition via 16S rRNA sequencing and untargeted metabolomics analysis. We assessed the impact of gut microbiota from sepsis patients on intestinal barriers in antibiotic-treated mice. Furthermore, We conducted spearman's correlation analysis to examine the relationship between metabolites and the severity of sepsis. Additionally, we performed animal experiments to validate the functionality of identified metabolites.The diversity of intestinal flora is decreased in patients with sepsis compared to the control group. Through fecal microbiota transplantation experiments, it was discovered that the gut microbiota derived from sepsis patients could induce intestinal damage in antibiotic-treated mice. Metabolomics analysis of the microbiota revealed a significant enrichment of the Valine, leucine, and isoleucine biosynthesis pathway. Further analysis showed a significant decrease in the abundance of L-valine in sepsis patients, which was negatively correlated with APACHE-II and SOFA scores. In sepsis mouse experiments, it was found that L-valine could alleviate sepsis-induced intestinal damage.Alterations in microbial and metabolic features in the gut can affect the severity of sepsis. Furthermore, L-valine can protect against sepsis-induced intestinal injury.